Assisted reproductive treatment outcomes of women with endometriomas: Either with or without previous ovarian surgery. Issue 12 (5th November 2021) - Sahin, Gulnaz; Acet, Ferruh; Biler, Alper; Meseri, Reci; Tavmergen Goker, Ege Nazan; Tavmergen, Erol
Abstract: Objective: The present study aimed to evaluate and compare the assisted reproductive technique (ART) outcomes of women with endometriomas either with or without prior endometrioma surgery. Materials and Methods: A total of 122 women with endometriomas underwent intracytoplasmic sperm injection‐embryo transfer (ICSI‐ET) at a tertiary IVF Center, between 2014 and 2019, were included in this retrospective study. Of this group, 38 patients had recurrent endometriomas and 84 patients had primary endometrioma without a previous endometrioma surgery. The outcomes of ART treatment including cancellation rates before ET, numbers of oocytes obtained, implantation, clinical pregnancy and live birth rates were compared between the groups. A logistic regression model including potential confounders as age and presence of male factor infertility was used to evaluate the possible effect of recurrent endometriomas on the live birth. Results: The baseline characteristics of the groups were similar. The poor ovarian response rate, defined as the harvest of fewer than four oocytes, was identified in 35.7% and 42.1% of primary and recurrent endometrioma groups, respectively. The implantation (27.2 ± 42.7% vs 24.1 ± 41.4%, P = .74), clinical pregnancy/ET (30.9% vs 27.6%, P = .93 ) and live birth rates/ET (22.1% vs 17.2%, P = .79) Conclusion: The ART outcomes of patients with primary and recurrent endometriomas do not seem different in terms of response to ovarian stimulation and live birth rates after ICSI. These results may indicate that the recurrence of the endometrioma might not have a further detrimental effect on ART outcome than the disease itself.